Ранньоскіфські наконечники списів із гофрованою втулкою - Скорий, С.А. (Археологія, 2023)
Статтю присвячено невеликій, але цікавій групі
скіфських залізних наконечників списів, що мають
на втулці гофрування у вигляді вузьких горизонтальних валиків. Наведено список таких знахідок,
що дало змогу окреслити територію, де вони трапляються (український Лісостеп) та час їх побутування (VII―VI ст. до н.е.). Призначення вказаної
особливості на списах суто утилітарне: для надійного закріплення на кінці втулки якогось бунчука,
штандарта, прообраза прапора майбутнього. Spears were the second most widespread (after the bow and arrows) weapon of the Scythian warriors. Now more than 1,000 iron
spearheads and shafts are known. Some spears were 3 m or more long, i.e. were combat weapons. Spears in Scythia, in contrast
to the eastern nomads, the Sauro-Sarmatians and the Saka, were a popular weapon, among both ordinary warriors and the elite.
Scythian spears, first of all, their tips, have been studied well. However, some of them have features that need to be explained.
That is the presence of horizontal ridges around the ends of the sockets of the spearheads, which were not primarily intended for
decoration. Few such tips have been found so far in the Ukrainian Forest-Steppe. They belong to the Scythian archaic period, and
more precisely to the period from the second half of the 7th to the beginning of the 6th centuries BC.
In author’s opinion, the ridges on spear sockets had a utilitarian purpose: they served to securely fasten tassels, possibly in
the shape of horse tails, or special badges that were prototypes of future flags. A similar tradition arose among the nomads of
Central Asia as early as the middle-second half of the 2nd millennium BC and then it had spread throughout the Eurasian region
and during later periods. The spears with bunchuks in the shape of horse or wolf tails have undoubtedly experienced evolution:
at first they were symbols of tribal and military unity, over time they began to play the role of a prestigious social marker – an
attribute of military leaders of different levels.
As a rule, notable Scythian warriors were buried in the graves where such spearheads were found. Apparently, spears with
tassels indicate that their owners were the heads of certain military contingents.
Given the synchronism of the mentioned burials with the period of the Scythian campaigns to the East, the appearance of
similar spears with tassels among the Scythians due to the Assyrian influence cannot be ruled out. In any case, spears with tassels
are attested on the reliefs of Assyria, although of an earlier time.